O debate da maioridade penal no Congresso Nacional: mapeamento das propostas legislativas - Kwen, Nara Josepin (2016)
The age of criminal responsibility is a topic that has been vastly debated in the Brazilian Congress. It is a dispute that goes beyond the legislative disagreement over the Proposal to amend the Constitution number 171/93 that aims to lower the age which a child or an adolescent can be held responsibility for their criminal actions. The discussion goes beyond the simple demand of reducing the age of criminal responsibility: there are much more issues and different bills from Congress that involves Youth Justice and making adolescents accountable for criminal charges as an adult. Acknowledging this scenario, this thesis aimed to 'map' and describe all the bills related to lowering the age of criminal responsibility. Databases and information from the House of Representatives and the Senate were exclusively used to identify and analyze each law in the making related to the issue. To support this endeavor, a brief study was made of the special legislation that involves Youth Justice and the juvenile criminal context in Brazil. Key issues, such as constitutional rights of Youth and criminal facts that explain the involvement of adolescents in crime, were explored and considered to facilitate the understanding of the analyzes that will be made about the bills that are discussed by the Brazilian Congress about the age of criminal responsibility